Soundspace: a manifesto - Ouzounian, G; Lappin, SA (Routledge, 2015)
The manifesto is a long-standing and powerful tool for challenge within architecture, deployed by those as diverse as Vitruvius and Frank Lloyd Wright (who proposed a Walt Whitman-inspired “Work Song” of 1896) to those publishing in blogs across the designing planet today. Manifestos are locations for dreaming, for the banging of shoes, for passion in words about the environment we invent. Our manifesto follows in that tradition of poetry and critical optimism in calling for a new architecture of soundspace. Here we wish to act as Markus Miessen’s “uninvited outsider” (Miessen 2010), a transgressive voice that disturbs the status quo beyond comfortable familiarity and brings together different types of thinkers and various modes of critique.[1] In this article we seek to probe “fundamental questions about how and for whom the built environment is produced and … conventional frameworks or oldestablished rules and regulations” through the interdisciplinarity that sound studies demands.[2] The ear to transgression is open.[3]